New and little-known families of Hemiptera Cicadomorpha from the Triassic of Central Asia—early analogs of treehoppers and planthoppers - Shcherbakov, Dmitry E. (Zootaxa, 2011)
One family, 12 monotypic genera, and 12 species of Triassic Cicadomorpha are described as new and two families, three genera, and three species are redescribed. All new taxa are from the Madygen Formation (Ladinian–Carnian) of Kyrgyzstan. Saaloscytinidae stat. nov. (Scytinopteroidea) includes Tingiopsis reticulata Becker-Migdisova, 1953 from Madygen and Saaloscytina Brauckmann et Schlueter, 1993 (= Chanarescytina Brauckmann, Martins-Neto et Gallego, 2006, syn. nov. = Chanarelytrina Martins-Neto et Gallego, 2006, syn. nov.) with one species from Germany and another from Argentina (Saaloscytina carmonae (Brauckmann, Martins-Neto et Gallego, 2006), comb. nov. = Chanarelytrina nana Martins-Neto et Gallego, 2006, syn. nov.). Maguviopseidae fam. nov. (Prosboloidea) comprises 2 subfamilies and 11 genera (all from Madygen): Sacvoyageinae subfam. nov. for Sacvoyagea ventrosa gen. et sp. nov. and Maguviopseinae subfam. nov. for Nonescyta mala gen. et sp. nov. and Nevicia imitans gen. et sp. nov. (Nonescytini trib. nov.), Maguviopsis kotchnevi Becker-Migdisova, 1953, Sitechka perforata gen. et sp. nov., Phyllotexta latens gen. et sp. nov., Cuanoma protracta gen. et sp. nov., Fasolinka beckermigdisovae gen. et sp. nov., Krendelia ansata gen. et sp. nov., Falcarta bella gen. et sp. nov., and Asiocula lima gen. et sp. nov. (Maguviopseini trib. nov.). Another family, Mesojabloniidae Storozhenko, 1992, is transferred from Grylloblattida to Hylicelloidea, and Fulgobole evansi gen. et sp. nov. and Scytachile emeljanovi gen. et sp. nov. are assigned to this family along with Mesojablonia kukalovae Storozhenko, 1992 (all three from Madygen). Homoplastic similarities of Saaloscytinidae and Maguviopseidae to Membracoidea and Mesojabloniidae to Fulgoroidea are discussed. The elaborate camouflage of these extinct hoppers and Dysmorphoptilidae is presumably due to increase of visual predation by small arboreal reptiles in the Triassic.